2014
DOI: 10.1371/journal.pone.0094042
|View full text |Cite|
|
Sign up to set email alerts
|

Education and WHO Recommendations for Fruit and Vegetable Intake Are Associated with Better Cognitive Function in a Disadvantaged Brazilian Elderly Population: A Population-Based Cross-Sectional Study

Abstract: Brazil has one of the fastest aging populations in the world and the incidence of cognitive impairment in the elderly is expected to increase exponentially. We examined the association between cognitive impairment and fruit and vegetable intake and associated factors in a low-income elderly population. A cross-sectional population-based study was carried out with 1849 individuals aged 65 or over living in São Paulo, Brazil. Cognitive function was assessed using the Community Screening Instrument for Dementia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…[ 21 ] Moreover, a study conducted in São Paulo found that fruit and vegetable intake (≥ 5 servings/day) was associated with a smaller prevalence of compromised cognition in older adults from lower-income areas (OR = 0.53; 95% CI 0.31 to 0.89). [ 22 ] Concordantly, a Chinese study found that adequate fruit and vegetable intake was associated with lower risk of compromised cognition in women (OR = 0.73; 95% CI 0.54 to 1.00). [ 38 ] In studies of Chen et al[ 33 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 21 ] Moreover, a study conducted in São Paulo found that fruit and vegetable intake (≥ 5 servings/day) was associated with a smaller prevalence of compromised cognition in older adults from lower-income areas (OR = 0.53; 95% CI 0.31 to 0.89). [ 22 ] Concordantly, a Chinese study found that adequate fruit and vegetable intake was associated with lower risk of compromised cognition in women (OR = 0.73; 95% CI 0.54 to 1.00). [ 38 ] In studies of Chen et al[ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil only two population-based studies[ 21 , 22 ] have investigated the association between fruit and vegetable intake and cognition in older adults. However, the studies were conducted in the Brazilian Southeast region and reflect the conditions of its population.…”
Section: Introductionmentioning
confidence: 99%
“…O’Brien et al followed up 15,467 women aged 70 or older for 6 years and observed that those with a higher long-term nut intake (>5 servings of nuts/week) had a significantly higher score of global cognitive function than that of non-consumers [ 43 ]. In the Chinese population, adults with a daily nut consumption of more than 10 g had 40% decreased odds of poor cognitive function (OR = 0.60, 95%CI: 0.43~0.84) among the sample of 4822 participants aged 55 and over [ 44 ]; those aged 65 years old and over with at least 1 serving/week of fish tended to have a better global cognitive function, found in a prospective cohort study with a follow-up of 5.3 years of 1566 participants [ 22 ]. Generally, the frequent consumption of fruit, vegetables, fish, and nuts was related to relatively healthy cognitive function, which was similar to results from our study that increased consumption of these foods decreased the odds of MCI and some of its subtypes, as well as was positively associated with higher scores of extensive cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…40 Nooyens et al 41 found no association between vitamin E and CF, although the mean age was younger at 55 compared with this study at 70.7. Pastor-Valero et al 42 found a significant association between age and CF but none with smoking status or hypertension. Inconsistencies in BMI and CF in several studies on elderly individuals were reported by Miller and Spencer.…”
Section: Covariatesmentioning
confidence: 95%